What are the demands of telegeriatrics medical services for elderly patients during the COVID-19 pandemic - Gong, Yu; Zhou, Jianyuan (Frontiers in Public Health, 2022)
PURPOSE: Elderly patients are associated a higher risk of nosocomial cross infection during the COVID-19 pandemic. Providing medical services and primary care for elderly patients is a worldwide challenge. A new telegeriatrics system was established to provide medical services and primary care for elderly patients treated by family physicians. This study is to describe the operation mechanism of the new system and investigate demands of telegeriatrics medical services for elderly patients treated by family physicians during the COVID-19 pandemic. METHODS: 1353 elderly patients (aged≥60) treated by family physicians were enrolled. Proportion of the top 10 diseases of elderly patients applying the new system was analyzed. Differences of main diseases between elderly patients applying telegeriatrics medical services and outpatients in hospital were compared. Differences between the new telegeriatrics system in our study and telemedicine systems of other studies in other countries were analyzed. RESULTS: Constituent ratios of chronic kidney disease, type 2 diabetes mellitus, coronary heart disease have the highest rate in elderly patients applying the new telegeriatrics system. Digestive diseases, cardiovascular diseases and neurology diseases were the top three diseases of the elderly outpatients. CONCLUSIONS: This is the first time that a new telegeriatrics system has been applied to provide medical services for elderly patients treated by family physicians during the COVID-19 pandemic. Chronic kidney disease, Type 2 diabetes mellitus and coronary heart disease were found to be the top three diseases of elderly patients applying telegeriatrics medical services during the COVID-19 pandemic which were different from the outpatients in general hospital. The new telegeriatrics system guarantees elderly patients get equal rights of medical services. Results will provide a basis for government health administrative department to formulate new telegeriatrics policies for elderly patients.